Damage Analysis of Leaf Springs Dump Truck Hino Dutro 130 HD - Joni Rahmadi; Fuazen; Adani AS (International Journal of Integrative Sciences, 2023)
Leaf springs that have been used for a long time will experience a decrease in the quality of the mechanical properties due to the dynamic loads that occur on this component. A comparison of two leaf spring materials is carried out, this is expected to be a solution to increase the strength and toughness of the leaf springs that have been used, the strength and carrying capacity of the damp truck is 8 tons. Spring damage mechanical strength Tensile Strength of Indospring Materials. In a Hino Dutro 130 HD brand car. The average tensile stress is 44.8 (HRC) The average tensile stress is 1407.8 N/mm2 The hardness in specimen 1 is 1407 N/mm2 in specimen 2, the hardness is 1408 N/mm2 in specimen 3, the result is hardness 1409 N/mm2 on specimen 4 with a hardness of 1407 N/mm2 and on specimen 5 the force value of hardness is 1408 N/mm2 Bending test of Indospring Material that has been carried out on Bending test data of Indospring Material to analyze the mechanical strength of spring damage. Strength of Indospring Material. In a Hino Dutro 130 HD brand car. Tensile force Hardness average 1407.8 N/mm2 HOP Material Bend, Indospring. In a Hino Dutro 130 HD brand car. The average hardness force is 1407.8 N/mm2. So that the strength of this material is feasible and good for use while loading trucks. Which is flat paved, so the weight of the cargo transported is not known with certainty. However, it can be estimated based on the carrying capacity, the weight of the cargo ranges from 7-10 tons, for one transport